KACAPI DALAM TEMBANG SUNDA CIANJURAN: KETERKAITANNYA DENGAN GAMELAN DEGUNG - Asep Nugraha (LP2M ISBI Bandung, 2017)
Kacapi in tembang sunda cianjuran related to gamelan degung. Bonang melodies in gamelan degung were adopted by Kacapi Indung, and peking melodies in gamelan degung were adopted by kacapi rincik. This paper tries to explore the relationship by comparing the melodic between the kacapi instruments and the instruments in the gamelan gamelan degung. The result was kacapi in tembang sunda cianjuran as miniature of the gamelan degung performance.